2015
DOI: 10.1128/aac.04320-14
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin Resistance and Its Mechanism in Neisseria gonorrhoeae Strains in Hyogo, Japan

Abstract: e Therapeutic options are limited for Neisseria gonorrhoeae infection, especially for oral drugs. The purpose of this study was to investigate the susceptibility of N. gonorrhoeae to oral azithromycin (AZM) and the correlation between AZM resistance-related gene mutations and MIC. We examined the AZM MICs of clinical strains of N. gonorrhoeae, sequenced the peptidyltransferase loop in domain V of 23S rRNA, and investigated the statistical correlation between AZM MIC and the presence and number of the mutations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…In gonococcal strains with the A-deletion in the 13-bp inverted-repeat sequence of the mtrR promoter (which overlaps the mtrCDE promoter at the −35 region), mtrR expression is abrogated while mtrCDE expression is elevated, most likely because of the greater binding affinity of RNA polymerase for mtrCDE ( 46 ). A report of 59 gonococcal isolates from Japan indicated that the A-deletion in the mtrR promoter was significantly associated with MICs of ≥0.5 mg/liter ( 47 ), a finding similar to that in our study, where >80% of both HL-AZM-R and low- to mid-level AZM-R isolates possessed this A-deletion. Missense mutations in the mtrR gene that result in, for example, a G45D mutation in the helix-turn-helix motif (located at amino acid [aa] 32 to aa 53) in the MtrR repressor can diminish the binding of the repressor to the mtrCDE promoter ( 48 , 49 ).…”
Section: Discussionsupporting
confidence: 90%
“…In gonococcal strains with the A-deletion in the 13-bp inverted-repeat sequence of the mtrR promoter (which overlaps the mtrCDE promoter at the −35 region), mtrR expression is abrogated while mtrCDE expression is elevated, most likely because of the greater binding affinity of RNA polymerase for mtrCDE ( 46 ). A report of 59 gonococcal isolates from Japan indicated that the A-deletion in the mtrR promoter was significantly associated with MICs of ≥0.5 mg/liter ( 47 ), a finding similar to that in our study, where >80% of both HL-AZM-R and low- to mid-level AZM-R isolates possessed this A-deletion. Missense mutations in the mtrR gene that result in, for example, a G45D mutation in the helix-turn-helix motif (located at amino acid [aa] 32 to aa 53) in the MtrR repressor can diminish the binding of the repressor to the mtrCDE promoter ( 48 , 49 ).…”
Section: Discussionsupporting
confidence: 90%
“…These antibiotics kill bacteria by either inhibiting cell wall synthesis through interacting with penicillin binding proteins (imipenem) or preventing protein synthesis through binding 50S (azithromycin) or 30S subunit (tetracycline and gentamicin) of the ribosome. Imipenem resistance is mainly caused by carbapenemases that degrade -lactam, [32][33][34] azithromycin resistance by methylase that alters the ribosomal target, [35] tetracycline resistance by overexpression of ribosomal protection proteins that remove tetracycline from the ribosome, [36] and gentamicin resistance by aminoglycosidemodifying enzymes. [37,38] A possible reason for reversal of antibiotic resistance phenotype and sensitization of the MDR bacteria toward antibiotic treatment is the polymer's ability in nonspecific binding to cytosolic enzymes (proteins) or genes, including those that are responsible for antibiotic resistance.…”
Section: Macromolecule Reverses Antibiotic Resistance Phenotypementioning
confidence: 99%
“…Similarly according to Wind et al study (2017), exposure to azithromycin was significantly associated with A39T or G45D mtrR mutations. This implies that, frequent azithromycin use in populations at high risk of contracting N. gonorrhoeae induces an increase in minimum inhibitory concentration (MIC), and may result in resistance [ 40 , 49 , 50 ]. A similar study in France also showed that mutations in domain V of 23S rRNA, encoded by the rrl gene, were associated with Azithromycin resistance by gonococcus [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Shigemura and his research team in Japan likewise reported that a deletion mutation of the mtrR promoter region is a possible mechanism of azithromycin resistance and may be a significant indicator for higher MICs (0.5 μg/ml or higher) in N. gonorrhoeae infection [51]. A recently released data showed a decreased antimicrobial susceptibility of gonococci to azithromycin that may limit effectiveness of the drug [52,53].…”
Section: Azithromycin Resistancementioning
confidence: 99%